Long-term outcomes of endoscopic submucosal dissection versus surgery for treating early gastric cancer of undifferentiated-type. Issue 22 (29th May 2020) - Guo, Anbing; Du, Chao; Tian, Shuni; Sun, Liangxu; Guo, Mingxiao; Lu, Lin; Peng, Lijun
Abstract : Abstract: Application of endoscopic submucosal dissection (ESD) for treating undifferentiated-type early gastric cancers (EGCs) remains controversial. Therefore, we aimed to compare long-term outcomes of ESD with those of surgery for patients with undifferentiated-type EGCs by a retrospective study. We retrospectively reviewed data of patients who underwent curative ESD or gastrectomy for undifferentiated-type EGCs between 2010 and 2017. Gastric cancers were undifferentiated-type adenocarcinoma without ulceration confined to the mucosal layer and 2 cm or smaller in size. Demographics, complications, recurrence cancer rates, and survival data were collected and compared. Forty patients who underwent curative ESD and 52 patients who underwent surgery were included. The median follow-up duration was 74.6 months. There was no significant difference of metachronous gastric cancer rate (5.0% vs 3.8%, P  = .75) or total cancer recurrence rate (10.0% vs 3.8%, P  = .33) between the 2 groups. The 5-year overall survival, disease-free survival, recurrence-free survival rates did not significantly differ between the 2 groups ( P  = .72, .26, .27 respectively). There were no gastric cancer-related deaths in either group. Long-term outcomes after curative ESD for undifferentiated-type EGCs that met the expanded indication were comparable to that achieved with surgery. ESD without additional surgery is an acceptable choice to treat undifferentiated-type EGCs that meet the curative criteria.